Aahuti: Nepalma Varnabyabastaa ra Barga Sangharsha (Varna System and Class Struggle in Nepal) - Khatri, Shanta Kumari (Himalayan Journal of Sociology and Anthropology, 2011)
Aahuti (nickname) : Nepalma Varnabyabastaa ra Barga Sangharsha (Varna System and Class Struggle in Nepal). Rajendra Maharjan (ed.). Samata Foundation Lalitpur, Nepal. (1st edition, 2010), ISBN: 978-9937-8372-0-0, Pages: 219 (LV), Script: Nepali, Soft Cover, Price: NRs 250.00. DOI: http://dx.doi.org/10.3126/hjsa.v4i0.4681 Himalayan Journal of Sociology and Anthropology Vol.IV (2010) 259-263